2015
DOI: 10.1002/jmv.24296
|View full text |Cite
|
Sign up to set email alerts
|

Human coronaviruses in severe acute respiratory infection (SARI) cases in southwest India

Abstract: Acute viral respiratory infections (AVRI) are a leading cause of morbidity and mortality among all age groups globally. Except for Influenza virus and Respiratory Syncytial virus, mostly viral aetiology of AVRI remains undiagnosed. Lately, human coronaviruses (HCoVs) have emerged as an important aetiology of AVRI. A laboratory based retrospective cross sectional study was conducted in which respiratory samples (throat swabs) of patients (n = 864), with Influenza negative SARI, of all age groups between Jan 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 11 publications
(15 reference statements)
1
10
1
Order By: Relevance
“…Endemic coronaviruses OC43, HKU1, NL63, and 229E can infect the upper respiratory tract of humans, causing mild or moderate disease. Severe symptoms like pneumonia are more commonly reported in children and patients with comorbidities, 4,5,[19][20][21][22] whereas in healthy adults, severe disease associated to these coronaviruses is rare. Accordingly, we found only one report describing infection with HCoV 229E associated with SARI in a healthy adult, who showed clinical improvement after treatment with corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endemic coronaviruses OC43, HKU1, NL63, and 229E can infect the upper respiratory tract of humans, causing mild or moderate disease. Severe symptoms like pneumonia are more commonly reported in children and patients with comorbidities, 4,5,[19][20][21][22] whereas in healthy adults, severe disease associated to these coronaviruses is rare. Accordingly, we found only one report describing infection with HCoV 229E associated with SARI in a healthy adult, who showed clinical improvement after treatment with corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Other respiratory viruses, like metapneumovirus (hMPV), bocavirus (HBoV), rhinovirus, and coronavirus (HCoV) 229E, NL63, HKU1, and OC43 are usually associated with mild disease; nonetheless, individuals infected with these viruses may also present SARI. [2][3][4][5] Of note, the severe acute respiratory syndrome (SARS) and the Middle East respiratory syndrome (MERS) epidemics that occurred in 2002 to 2003 and 2012, respectively, and the current coronavirus disease-2019 (COVID- 19) pandemic are caused by zoonotic transmission of highly pathogenic coronaviruses, namely, SARS-CoV, MERS-CoV, and SARS-CoV-2, respectively. 6,7 Epidemiological surveillance of respiratory viruses is the basis for disease control, prevention, and preparedness.…”
Section: Introductionmentioning
confidence: 99%
“…Acute respiratory tract infections cause substantial mortality and morbidity in all ages globally. Apart from influenza and respiratory syncytial viruses (RSVs), several other respiratory viruses remain largely undiagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…Acute respiratory tract infections cause substantial mortality and morbidity in all ages globally. Apart from influenza and respiratory syncytial viruses (RSVs), several other respiratory viruses remain largely undiagnosed. Understanding and defining the contribution of viral etiologies of severe respiratory illness in countries like South Africa that have a high burden of human immunodeficiency virus (HIV) infections and associated acquired immunodeficiency syndrome may be important for health management and planning.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus infections are not uncommon among children in India. 3 hospital-based studies were done in past to determine the incidences of coronavirus infections [3,8,12]. These reports suggested that there are cases of human coronavirus infections in India albeit at low rate.…”
Section: Risk Factors and Transmission Dynamics Favorable For Diseasementioning
confidence: 99%